Acceptability and feasibility of a chronic breathlessness diagnostic clinical algorithm in Australian primary care - Sunjaya, Anthony Paulo; Martin, Allison; Arnott, Clare; Di Tanna, Gian Luca; Gianacas, Chris; Marks, Guy; Jenkins, Christine (Australian journal of general practice, 2024)
Chronic breathlessness is a frequent diagnostic challenge in primary care. Our aim is to evaluate the feasibility of a stepwise breathlessness diagnostic algorithm for primary care. This mixed-methods study included: (1) a general practitioner (GP) nominal group technique study; (2) focus groups on GPs' views on the algorithm; and (3) analysis of algorithm alignment against patterns of diagnostic referrals and diagnoses of breathlessness presentations (2014-19) from the MedicineInsight primary care electronic health record (EHR) dataset of 1,961,264 patients (405 general practice sites). All the tests in our algorithm, except for echocardiography, were ranked in the top 10 tests used by most GPs for patients presenting with chronic breathlessness. Themes from the focus group include similarity with current practice and test accessibility. Analysis of EHR diagnostic referrals revealed that all tests in the algorithm are regularly utilised and covered the major tests needed for breathlessness diagnoses recorded. The results of the three studies support the acceptability and feasibility of the clinical algorithm in primary care.